CENTRAL ASIA: THE PLANET’S PIVOT AREA (The Axis of the World) - Duarte, Paulo (2024)
This article aims to highlight the major geopolitical and geostrategiccharacteristics of Central Asia. The central argument is that this is a region of greatimportance in the current economic arena as a result of its strategic position as a linkbetween East and West, a space of competition and affirmation of the great powers, butalso as a result of its extraordinary oil reserves.